Removal of microcystin-LR from aqueous solutions using % burn-off activated carbon of waste wood material - Hena, Sufia; Ismail, Norli; Mohammed, Issam Ahmed; Ahmad, Aiman; Bhawani, Showkat (IWA Publishing, 2014)
The activated carbon (AC), prepared at different burn-off rates, showed a high uptake of methylene blue. At 93% burn-off, methylene blue uptake was 620 mg/g. Adsorption capacity of microcystin-LR onto rubber wood AC was investigated in a batch system by considering the effects of various parameters like contact time, initial concentration, pH and temperature. Microcystin-LR removal is pH dependent and found to be highest at pH 2.5. Increases in adsorption capacity with increase in temperature indicate that the adsorption reaction is endothermic. Based on this study, the thermodynamic parameters like standard Gibb's free energy (ΔG°), standard enthalpy (ΔH°) and standard entropy (ΔS°) were evaluated. A pseudo second order model was found to explain the kinetics of microcystin-LR adsorption most effectively. The rate of intraparticle diffusion was also evaluated. The Langmuir and Freundlich isotherms were used to describe the adsorption equilibrium studies of rubber wood AC at different temperatures. The Langmuir isotherm shows better fit than Freundlich isotherms in the temperature range studied. The results show that the rubber wood AC can be efficiently used for the removal of microcystin-LR from water. In order to investigate the possibility of regeneration and reuse of exhausted adsorbent, desorption studies were also performed.